Complex digital learning environments in a postdigital age - Pilgaard, Michal; Davidsen, Jacob (Proceedings of the International Conference on Networked Learning, 2026)
This paper develops and discusses a conceptual approach to understanding complex digital learning environments within networked learning. Based on previous studies focusing on makerspaces published within the networked learning community this paper explores the makerspace phenomenon in education and initially discusses and suggests that learning environments equipped with digital technologies such as makerspaces could be defined and approached as a ‘complex digital learning environment’. The notion of complexity is particularly useful for understanding environments such as makerspaces because they integrate heterogeneous elements, technological tools, spatial configurations, pedagogical approaches, and social practices, that together shape learning opportunities and constraints. Makerspaces can be recognised as environments that provide access to various tools and digital technologies, enabling users to explore and make artifacts. Makerspaces appear in multiple forms within educational contexts exhibiting various configurations. Although the notion of educational makerspaces is subject to interpretations, they may often be associated with digital technologies such as 3D printers, laser cutters, microcontrollers and robotics. A range of actors across research, practice, and policy have argued that makerspaces in education may serve as a catalyst for unlocking possibilities for teaching and learning activities and outcomes. Interpretations of makerspaces in education may foster networked engagement and collaborative learning; however, they may also foster boundaries for both educators and the learners, both in terms of context, digital technologies and pedagogy. By conceptualising makerspaces as complex digital learning environments, the aim is to move beyond instrumental or purely spatial understandings and instead emphasise the dynamic interrelations between material, digital, and human actors. This perspective allows to foreground how networked learning unfold within and across these environments, and how they are conditioned by both enabling and constraining factors. In addition, this paper argues that emphasising the complexity and potential boundaries of physical digital learning environments may support a shared ground for networked engagement with possibilities and the boundaries of such settings when designing for learning. In particular, acknowledging boundaries such as institutional constraints, access to technologies, pedagogical preparedness, and digital literacy can help educators and researchers collaboratively negotiate design principles that are sensitive to local conditions while still fostering meaningful connections across networks. Thus, the conceptualisation aims to contribute to the networked learning discourse by offering an analytical lens for studying and designing learning ecologies that are simultaneously digital, physical, and networked.